Party Positions about European Integration in Germany: An Electoral Quandary?. Issue 1 (2nd January 2017) - Rohrschneider, Robert; Whitefield, Stephen
Abstract : Given the rise of EU-scepticism in Germany and elsewhere, spatial models suggest that the SPD and the CDU/CSU have incentives to move towards a more critical position about integration. However, mainstream parties have developed a pro-integration reputation over several decades so it is difficult for them to adopt a stance reflecting outright opposition to Europe's integration. A comparison of party positions in 2008 and 2013 shows that the SPD hardly changed its policy stances on EU issues, whereas the CDU/CSU moved noticeably to a more EU-critical stance. However, situating German parties within the West European universe of party families shows that both remain quite positive about integration. The upshot of this is to illustrate the 'blind corner' of party representation on integration issues in the German party system which created electoral opportunities for the Euro-sceptic AfD.